An integrative toolbox to unlock the structure and dynamics of protein–surfactant complexes. Issue 9 (20th July 2020) - Sanchez-Fernandez, Adrian; Diehl, Carl; Houston, Judith E.; Leung, Anna E.; Tellam, James P.; Rogers, Sarah E.; Prevost, Sylvain; Ulvenlund, Stefan; Sjögren, Helen; Wahlgren, Marie
Abstract : A holistic approach is developed for investigating the interaction mechanism between proteins and surfactants in solution. Abstract : The interactions between protein and surfactants play an important role in the stability and performance of formulated products. Due to the high complexity of such interactions, multi-technique approaches are required to study these systems. Here, an integrative approach is used to investigate the various interactions in a model system composed of human growth hormone and sodium dodecyl sulfate. Contrast variation small-angle neutron scattering was used to obtain information on the structure of the protein, surfactant aggregates and surfactant–protein complexes. 1 H and 1 H– 13 C HSQC nuclear magnetic resonance spectroscopy was employed to probe the local structure and dynamics of specific amino acids upon surfactant addition. Through the combination of these advanced methods with fluorescence spectroscopy, circular dichroism and isothermal titration calorimetry, it was possible to identify the interaction mechanisms between the surfactant and the protein in the pre- and post-micellar regimes, and interconnect the results from different techniques. As such, the protein was revealed to evolve from a partially unfolded conformation at low SDS concentration to a molten globule at intermediate concentrations, where the protein conformation and local dynamics of hydrophobic amino acids are partially affected compared to the native state. At higher surfactant concentrations the local structure of the protein appears disrupted, and a decorated micelle structure is observed, where the protein is wrapped around a surfactant assembly. Importantly, this integrative approach allows for the identification of the characteristic fingerprints of complex transitions as seen by each technique, and establishes a methodology for an in-detail study of surfactant–protein systems.